Überholspur oder Abstellgleis? Studie zum europäischen Schienenpersonenverkehr 2009. - Holsten, Jan Ulrik; Pulver, Thorsten (DVV Media Group, 2009)
Das Personenverkehrsaufkommen ist seit 1995 in den EU-27 Staaten um über 20 % gestiegen. Von dieser Entwicklung profitierte auch der Schienenpersonenverkehr. Trotz seines relativ geringen Marktanteils von deutlich weniger als 10 % (ohne Tram und Metro) hat der Schienenpersonenverkehr eine besondere Bedeutung, weil er beispielsweise Anteil an der öffentlichen Daseinsvorsorge hat und im Vergleich zum Individual- und Flugverkehr in geringerem Umfang zu externen Kosten beiträgt. Im Gegensatz zum Schienengüterverkehr existiert für den Schienenpersonenverkehr bislang keine einheitliche, durchgängige Rechtsgrundlage, auf der die Akteure ihre Leistungen erbringen könnten. Mit dem dritten Eisenbahnpaket soll sich diese Situation nach dem Willen der Europäischen Kommission ändern.

Industry analysts tend to think that European railways are well placed to compete for customers in the coming years. This is the outcome of a study jointly undertaken by the international consultancy firm Droege & Comp. and Professor Gerd Aberle, with the involvement of Europe's top decision makers, (former) state owned and privately owned railway companies and market-related institutions. A clear majority of ninety-three per cent of the respondents questioned is convinced that the railways' competitiveness in long-haul traffic versus air transport - its principal challenger - will be enhanced, while eighty per cent anticipate gains in market share. Seventy-seven per cent of those questioned think it likely that, also in short-haul traffic, the railways' competitive strength vis-a-vis individual motorized transport will improve. In the case of long-haul traffic, the railways are able to retain their place in national and intra-European markets - vis-a-vis air travel - over routes of up to 450 km. To safeguard their competitive standing in this sector, and to increase their market share, the high speed rail network should - by necessity - be expanded in future. While continuously expanding their short- and long-haul traffic rail operators make efforts to enhance their operative efficiency and reduce costs. By resorting to 'outsourcing', a further reduction in value creation could be avoided. In almost all cases, this option seems to be acceptable to a majority of eighty per cent of the respondents. Rail operators will continue to rely on yield management, while using customer loyalty schemes to foster traffic growth, especially in the long-haul sector.
On the way up or shunted into a siding?
Keywords: Verkehr; Verkehrsentwicklung; Schienenverkehr; Schienenpersonenverkehr; Marktanteil; Personenverkehr; Wirtschaftlichkeit; Wettbewerb; Verkehrsmarkt; Marktzugang; Verkehrsträger; Verkehrsanteil; Trend; Effizienzsteigerung; Kundenorientierung